1975
DOI: 10.1002/jsfa.2740260615
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiration and soluble carbohydrates during the post‐harvest storage of mushrooms (Agaricus bisporus)

Abstract: The COz production and soluble carbohydrate content were studied in the cultivated mushroom (Agaricus bisporus) during storage at 18 "C. The pattern of postharvest respiration was seen to be dependent on the maturity of the sporophore at harvest. A post-harvest respiratory peak was observed and this appeared to correspond with the phase of rapid gill development which occurs after harvest of immature, fruit bodies. The disappearance of significant quantities of mannitol from the sporophore during storage seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 10 publications
4
103
0
Order By: Relevance
“…The present study has shown that changes in the activity of two other enzymes, considered to be responsible for the carbohydrate supply to the developing sporophore (namely, trehalase and glycogen phosphorylase), also accompany fiushing and exhibit a similar correlation with it. In each case, the enzymes extracted from stage 1 sporophores (Hammond & Nichols, 1975 reach their maximum activity when a flush reaches its peak, as defined by yields of stage 2 to 4 sporophores. Minimum activity corresponds to the period between flushes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown that changes in the activity of two other enzymes, considered to be responsible for the carbohydrate supply to the developing sporophore (namely, trehalase and glycogen phosphorylase), also accompany fiushing and exhibit a similar correlation with it. In each case, the enzymes extracted from stage 1 sporophores (Hammond & Nichols, 1975 reach their maximum activity when a flush reaches its peak, as defined by yields of stage 2 to 4 sporophores. Minimum activity corresponds to the period between flushes.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol functions as the endogenous carbon and energy source to enable sporulation of the oocysts outside of the host (2). Similarly, in A. bisporus fruiting bodies, mannitol contributes up to 50% of the dry weight and is believed to be the main source of carbon and energy in the mushroom after harvest (16).…”
mentioning
confidence: 99%
“…bisporus, the stipe lengthens and the cap expands to expose the developing gills (Hammond & Nichols, 1975). Treatment with polyoxin D or cycloheximide reduced this expansion ( Table I) ; sporophores treated with antibiotics expanded only some 12 to 13 % over 2 days.…”
Section: Resultsmentioning
confidence: 99%